Individual-Psychological Characteristics of Management Decision-Making - Sodiqova Gulbarno Odiljon qizi (European Science Publishing, 2023)
In this article, the individual and psychological characteristics of management decision-making were studied, psychological aspects of decision-making, scientific-theoretical foundations were analyzed and relevant conclusions were drawn.
Keywords: management, decision-making, individual-psychological characteristics.